Understanding Parent Reactions to Coming Out as Lesbian, Gay, or Bisexual: A Theoretical Framework. Issue 2 (June 2017) - Chrisler, Alison J.
Abstract: Existing theories and the development of new theoretical models have been used to better understand the experiences of parents who have lesbian, gay, and bisexual children. However, these models tend to only capture a single aspect of the parent experience. This article combines existing theory and data from published research studies to propose a theoretical framework that can be used to explain parent reactions to coming out. Next steps include refining and empirically testing the proposed framework.